(3bQI GdYjhf aj CNHGQ Gdjef Gdejehfs - (3CHhYHO Gddg YHO GdQMef Hf Ydj Hf eMeO Hf YeQ Hf Ydj Hf jhSa hLjg GdOjf GdTjHGfi GdRHjOi Hf GdHOjYs; (3Ydj Hf GdMSf Hf CHj HcQ Hf GdMSf GHf hgGS GdNRQLj GdRHjOj, CHh GdMSf ehab GdOjf,J (B812 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi NU bWQ Gdjef Gdejehf HGdCeGf Ce HYO , aEf Yde GdJGQjN Yde YXje GdebOGQ s
(3BNQgG (B:s
(3NGQL UfYGA ai QHjY GdBNQ eSJTgOkG ai YTQg GdChGNQ JeJ , hGddg CYde s
(3GfXQ HQbe (B" 375" (3JGQjNs
(3fSNI KGfjIs
(3fbdJ ef fSNI YHGS CafOi GdYRGhjs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs